2022
DOI: 10.1021/acs.macromol.2c02013
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition of the Surface Monolayer of Polystyrene Films with Different Film Thicknesses and Supporting Surfaces

Abstract: Surface glass-transition temperature (T g surf) and transition width (W) within 1 nm of the surface were measured by monitoring a qualitative change in the contact angle or density of end-groups (by time-of-flight secondary ion mass spectrometry) with temperature. Polystyrene (PS) films with various thicknesses (h) and molecular weights were studied. For unannealed PS supported on oxide-coated silicon or poly(dimethyl siloxane) with h > ∼60 nm, T g surf approached a plateau value of ∼25 K below the bulk T g; b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 80 publications
4
10
0
Order By: Relevance
“…After 5 h preannealing at 393 K, T g surf became independent of h (open squares). Because the same preannealing effect was observed for PS-SiO x with a different M w of 1119 kg/mol in our previous experiment, 8 the above result suggests the generality of the observed preannealing effect on the T g surf of PS−SiO x . Focusing on the data of the h = 10 nm films in Figure 2, we notice that T g surf did not recover the steady-state value within the 5 h preannealing at 333 K. We thus studied variations of T g surf with t ANN at 333 K.…”
Section: Observation Of the Effect Of Preannealing On Thesupporting
confidence: 85%
See 2 more Smart Citations
“…After 5 h preannealing at 393 K, T g surf became independent of h (open squares). Because the same preannealing effect was observed for PS-SiO x with a different M w of 1119 kg/mol in our previous experiment, 8 the above result suggests the generality of the observed preannealing effect on the T g surf of PS−SiO x . Focusing on the data of the h = 10 nm films in Figure 2, we notice that T g surf did not recover the steady-state value within the 5 h preannealing at 333 K. We thus studied variations of T g surf with t ANN at 333 K.…”
Section: Observation Of the Effect Of Preannealing On Thesupporting
confidence: 85%
“…To counter any changes in the surface chemistry of the films caused by surface relaxations upon the preannealing process (which may impair the T g surf measurement), before conducting T g surf measurement of the preannealed films, we “renewed” the surface of the films by spin-coating a drop of acetic acid on the surface and drying the films in vacuum (∼1 Pa) at room temperature for 12 h. As illustrated by the data of the PS151k-SiO x films preannealed at 393 K for 5 h (open squares, Figure ), the acetic acid treatment did not produce obvious qualitative change to the location or width of the surface glass transition. (See also Figure S3 of ref . )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The past three decades have witnessed intense research focused on nanoscale confinement effects of polymeric glass-formers. Studies have reported that a broad range of properties, including the glass-transition temperature ( T g ), surface viscosity, small-mole...…”
Section: Introductionmentioning
confidence: 99%
“…The T g -confinement effect has been the most extensively studied of these properties since it was first reported in detail in 1994 by Keddie et al for polystyrene (PS) ultrathin films supported on silicon . For polymers like PS lacking attractive interactions with the substrate, films of some tens of nanometers in thickness commonly exhibit a reduction in T g compared to the bulk value, a fact that is widely explained by enhanced chain dynamics near the free surface. , Specifically, the free surface reduces the level of cooperativity requirements for chain dynamics, which increases the local chain mobility, leading to a lower local T g and thereby decreasing the overall film T g . ,,,,,,, The free-surface effect can propagate several tens of nanometers into the interior of a PS film. ,,, …”
Section: Introductionmentioning
confidence: 99%